Ecological education: Concrete efforts in applying the concept of ecological citizenship in Malang - Syahri, Mohamad; Wibowo, Arif Prasetyo; Pratiwi, Arini Dyah Mustika; Tinus, Agus (Jurnal Civics: Media Kajian Kewarganegaraan, 2022)
The research aims to describe the role of schools in applying the concept of ecological citizenship at High Schools in Malang, analyze the implications of applying the concept of ecological citizenship to the environmental care character of students at High Schools in Malang, to find out the supporting and inhibiting factors in the application of the concept of ecological citizenship at SMP Negeri 10. Poor. This research method uses a qualitative type of research using a qualitative descriptive research design by managing research data in a descriptive form described in detail. The results of the study show: (1) the role of schools in implementing the concept of ecological citizenship in schools is quite good and is implemented through the vision and mission, school innovation programs, and school culture, then learning activities that are integrated into all subjects and extracurricular activities of eco generation, (2) The implications for student behavior are that students can apply their habits in school by having responsibility for their environment so that they can apply these habits outside of school in a sustainable manner, (3) factors that support and inhibit school success are the participation of all school members to commit together to protect the school environment. In addition, there is support from parents, school committees, related agencies, institutions, universities, and stakeholders who help develop school innovation programs and manage school infrastructure.